(untitled) - Hoff, Trygve J. B. (London, 1949)
Written by Trygve J. B. Hoff. Dr Hoff's 1938 book and Professor Vaughn's important introduction establish the theoretical impossibility of socialism: a system empirically in ruins but still advocated by many.
Keywords: Economic policy,Socialism,Chính sách kinh tế,Chủ nghĩa xã hội